2010
DOI: 10.1258/ht.2010.010013
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative investigation into the rehabilitation experience of patients following wrist fracture

Abstract: Bamford, Rachael and Walker, Dawn-Marie (2010) A qualitative investigation into the rehabilitation experience of patients following wrist fracture. Hand Therapy, 15 (3). pp. 54-61. ISSN 1758-9983 Access from the University of Nottingham repository: http://eprints.nottingham.ac.uk/1431/1/bamford_walker.PDF Copyright and reuse:The Nottingham ePrints service makes this work by researchers of the University of Nottingham available open access under the following conditions. This article is made available under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 18 publications
(41 reference statements)
4
26
0
3
Order By: Relevance
“…A recent scoping review (Burley, Di Tommaso, Cox & Molineux, 2018) revealed that patients with hand injuries experienced occupational issues and found rehabilitation informed by an occupational perspective to be motivating (Bamford & Walker, 2010;Cheung, Clemson, O'Loughlin & Shuttleworth, 2016;Engstrand, Krevers & Kvist, 2015). Other themes from the scoping review included: the assumption that a bottom-up, biomechanical approach would improve occupational performance; a high focus placed on occupational outcome measures; and the use of informal discussion as an occupational strategy (Powell & Von Der Heyde, 2014;Weinstock-Zlotnick & Bear-Lehman, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A recent scoping review (Burley, Di Tommaso, Cox & Molineux, 2018) revealed that patients with hand injuries experienced occupational issues and found rehabilitation informed by an occupational perspective to be motivating (Bamford & Walker, 2010;Cheung, Clemson, O'Loughlin & Shuttleworth, 2016;Engstrand, Krevers & Kvist, 2015). Other themes from the scoping review included: the assumption that a bottom-up, biomechanical approach would improve occupational performance; a high focus placed on occupational outcome measures; and the use of informal discussion as an occupational strategy (Powell & Von Der Heyde, 2014;Weinstock-Zlotnick & Bear-Lehman, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Keeping in mind that the participants' main focus was on being able to perform everyday life activities again, it seems natural that they wanted a holistic evaluation. Other studies with patients with hand-related disorders also find the importance of linking the objective measurements of body function to everyday life activities [66].…”
Section: Evaluation Of Outcomes From the Patient´s Perspectivementioning
confidence: 99%
“…Overview of wrist fractures. Wrist fracture is a common traumatic condition and represents the majority of upper limb fractures (Bamford & Walker, 2010). An injury to the wrist can impact occupational performance because the wrist plays an important role in many functional activities (Brodeur-Lyons & Oaks, 2009).…”
Section: Wrist Fracturementioning
confidence: 99%
“…The participants advocated that occupational therapy was a key element in their motivation. Hence, Bamford and Walker (2010) concluded that participants who received instruction from an occupational therapist were more likely to be compliant with their home program.…”
Section: Adherence To Home Programmentioning
confidence: 99%
See 1 more Smart Citation